2007
DOI: 10.1529/biophysj.107.107847
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Organization in Canine Myxomatous Mitral Valve Disease: An X-Ray Diffraction Study

Abstract: Collagen fibrils, a major component of mitral valve leaflets, play an important role in defining shape and providing mechanical strength and flexibility. Histopathological studies show that collagen fibrils undergo dramatic changes in the course of myxomatous mitral valve disease in both dogs and humans. However, little is known about the detailed organization of collagen in this disease. This study was designed to analyze and compare collagen fibril organization in healthy and lesional areas of myxomatous mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…MV leaflets have extensive passive collagen fiber networks (5,11,12,15,18), and the stress-strain relationship of isolated leaflets (3,14,22,27) is consistent with the material properties of passive collagen fibers. Our recent study (21), however, suggested that leaflet stiffness in the beating heart (slope of the leaflet stress-strain curve) was much greater than that of passive tissue, and studies of freshly isolated, oxygenated, stimulated leaflets in myographs (39) and in open hearts on cardiopulmonary bypass (CBP) (7,32) have suggested that the mechanical properties of MV leaflets may be altered actively.…”
mentioning
confidence: 55%
“…MV leaflets have extensive passive collagen fiber networks (5,11,12,15,18), and the stress-strain relationship of isolated leaflets (3,14,22,27) is consistent with the material properties of passive collagen fibers. Our recent study (21), however, suggested that leaflet stiffness in the beating heart (slope of the leaflet stress-strain curve) was much greater than that of passive tissue, and studies of freshly isolated, oxygenated, stimulated leaflets in myographs (39) and in open hearts on cardiopulmonary bypass (CBP) (7,32) have suggested that the mechanical properties of MV leaflets may be altered actively.…”
mentioning
confidence: 55%
“…Unstable, immature and abnormally crosslinked collagen molecules were identified. 66,67 Furthermore, an accumulation of proteoglycans, lipids and hexosamines was detected in canine MMVD. 8,68,69 Immunohistochemical studies in mild canine MMVD showed an irregularly split basement membrane.…”
Section: Extracellular Matrixmentioning
confidence: 95%
“…4,17,18,63 The anterior to posterior length ratio has been reported as 1.7 to 1, 38 The chordae tendineae and papillary muscles Effective closure of the mitral valve requires complex, temporal, and geometric coordination of the left atrioventricular annulus, mitral leaflets, and subvalvular apparatus. Each mitral valve leaflet is adjoined to the anterior or posterior papillary muscles or occasionally, directly to the ventricular wall by fibrous chords, the chordae tendineae.…”
Section: Gross Featuresmentioning
confidence: 99%